Preparation method of mesoporous resin-based silicon carbon precursor
By initially treating mesoporous resin and silica raw materials and preparing conductive coatings with corn starch, maleic anhydride and other materials, the surface area performance and thermal stability problems caused by grinding are solved, and the specific surface area and thermal stability of mesoporous resin-based silicon carbon precursors are significantly improved.
Patent Information
- Application Number
- CN202411925308.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
AI Technical Summary
During the preparation of existing mesoporous resin-based silicon carbon precursors, grinding treatment leads to contact friction on the raw material surface, affecting specific surface area performance and thermal stability.
By initially treating the mesoporous resin and silica raw materials, the corrosiveness of the chromic acid solution is used to generate rich pore structures, and compatibility is enhanced through ball milling and ultrasonic dispersion technology. Conductive coatings are prepared in combination with materials such as corn starch and maleic anhydride to improve the specific surface area and thermal stability of the precursor.
The specific surface area performance and thermal stability of the mesoporous resin-based silicon carbon precursor are significantly improved, and its performance in the subsequent preparation process is enhanced.
Smart Images

Figure CN119592095A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon-carbon precursors, in particular to a method for preparing a mesoporous resin-based silicon-carbon precursor. Background Art
[0002] A silicon-carbon precursor is an intermediate substance that can be converted into a silicon-carbon composite material after specific treatment. It is usually a compound or mixture containing silicon and carbon elements. During high-temperature pyrolysis, chemical vapor deposition and other processes, the silicon and carbon elements in the precursor will react and rearrange their structures, eventually forming a silicon-carbon composite material.
[0003] In the prior art, in the preparation process of the mesoporous resin-based silicon-carbon precursor, it is necessary to grind the raw materials of the precursor so as to finally mix them to obtain the precursor. However, during the grinding process, the surfaces of the small particles of the raw materials are contacted and rubbed with each other and polished smooth, which affects the specific surface area performance of the precursor. Based on this, the present invention provides a method for preparing a mesoporous resin-based silicon-carbon precursor. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a mesoporous resin-based silicon-carbon precursor, which effectively improves the specific surface area performance and thermal stability of the mesoporous resin-based silicon-carbon precursor.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a mesoporous resin-based silicon-carbon precursor, comprising the following steps: S1: selecting a mesoporous resin raw material, and obtaining a preliminarily treated resin after treatment, and selecting a silica raw material, and obtaining a preliminarily treated silica after treatment; S2: preparing the first mixed material for standby use; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: preparing the second mixed material for standby use; S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mixing the first prepared material obtained in step S3 with the second prepared material obtained in step S5 to obtain a mesoporous resin-based silicon-carbon precursor.
[0006] Furthermore, the preliminary treated resin in step S1 is prepared by the following method: weighing the mesoporous resin as needed, crushing it into granular mesoporous resin, then soaking the mesoporous resin in chromic acid solution for 24 to 36 hours, washing it with deionized water for 5 to 7 times after soaking, sending it into an oven for drying, and then grinding and sieving to obtain the preliminary treated resin.
[0007] Furthermore, the preliminary treated silica in step S1 is prepared by the following method: weigh silica raw materials as needed, crush, grind and sieve the silica raw materials to obtain silicon powder, send the silicon powder into a ball mill for ball milling, add a blending material during the ball milling process, and the mass of the blending material is 55-65% of the mass of the silicon powder. After the ball milling treatment is completed, the silicon powder is placed in an ultrasonic disperser for treatment, and the ultrasonic frequency is set to 60-100 kHz and the time is 8-10 min. After the ultrasonic treatment is completed, the preliminary treated silica is obtained.
[0008] Furthermore, the first mixed material in step S2 is prepared by the following method: corn starch is selected as a raw material, the corn starch is mixed with a copper sulfate solution, the concentration of the copper sulfate solution is 2-4%, the mass ratio of the corn starch to the copper sulfate solution is 1: (2-4), after the mixing reaction for 10-20 minutes, the first mixed material is obtained after filtering and drying.
[0009] Furthermore, the second mixed material in step S4 is prepared by the following method: glycerol and anhydrous ethanol are mixed, the concentration of glycerol is 5-7%, and the mass ratio of glycerol to anhydrous ethanol is 1:(4-6); after the mixing is completed, the mixture is heated in a water bath to 65-75%, and kept warm for 15-25 minutes; then corn starch is added, and the mass of corn starch is 60-70% of the glycerol; after the addition, the temperature is raised to 85-95°C, and stirring is continued; after keeping stirring for 8-12 minutes, the mixture is cooled to room temperature to obtain the second mixed material.
[0010] Furthermore, in step S1, the preheating temperature of the oven is set at 55-65° C., and the temperature is raised to 90-100° C. and then kept warm for 6-8 hours.
[0011] Furthermore, the formulation is prepared by the following method: maleic anhydride is mixed with a xylene solution, the concentration of the xylene solution is 20-40%, the mass ratio of the maleic anhydride to the xylene solution is 1:(4-6), after mixing, the mixture is allowed to react for 40-50 minutes, and the reaction product is filtered, washed, and dried to obtain the formulation.
[0012] Furthermore, the particle size of the preliminarily treated resin after screening is ≤100 μm.
[0013] Furthermore, the particle size of the preliminarily treated silica after ball milling is ≤75 μm.
[0014] Furthermore, the mixing treatment method in step S6 is: mixing the first prepared material with the second prepared material, wherein the mass ratio of the first mixed material to the second mixed material is 1:(0.5-0.7), and after mixing, the mixed materials are sent to an ultrasonic disperser for treatment, and the ultrasonic frequency is set to 80-120 kHz and the time is 12-16 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention preliminarily treats silica raw materials and mesoporous resin raw materials. After the mesoporous resin is soaked in a chromic acid solution, the corrosiveness of the chromic acid solution can cause an oxidation-reduction reaction with the surface of the mesoporous resin, so that the mesoporous resin is corroded to form a rich pore structure. During the ball milling process, the silica raw materials are modified by adding a blending material and using maleic anhydride to modify silicon powder. The anhydride groups in the maleic anhydride react with the hydroxyl groups on the surface of the silicon powder to form an ester bond, which can enhance the compatibility of the silicon powder with the preliminarily treated resin, so that the prepared mesoporous resin-based silicon-carbon precursor has good specific surface area performance, thereby improving the performance of the precursor in the subsequent preparation process.
[0016] 2. The present invention adds a first mixed material, and the first mixed material is prepared by adding corn starch as a raw material. After being treated with a copper sulfate solution, the corn starch can be effectively wrapped on the surface of the raw material to form a conductive coating. In the subsequent heating treatment, the corn starch is heated and gelatinized. The gelatinized conductive coating can be firmly attached to the surface of the powder raw material of the precursor, has good wrapping properties, and thus improves the thermal stability of the precursor. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A flow chart of a method for preparing a mesoporous resin-based silicon-carbon precursor is proposed for the invention. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.
[0020] This embodiment provides a method for preparing a mesoporous resin-based silicon-carbon precursor, comprising the following steps: S1: Selecting a mesoporous resin raw material, the mesoporous resin raw material is a mesoporous resin with a pore size of 2 to 50 nm, and after treatment, obtaining a preliminarily treated resin, and selecting a silica raw material, and after treatment, obtaining a preliminarily treated silica; S2: preparing the first mixed material for standby use; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: preparing the second mixed material for standby use; S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mixing the first prepared material obtained in step S3 with the second prepared material obtained in step S5 to obtain a mesoporous resin-based silicon-carbon precursor.
[0021] The preliminary treated resin in step S1 is prepared by the following method: weigh the mesoporous resin as needed, crush it, and process it into granular mesoporous resin, then soak the mesoporous resin in chromic acid solution for 24 to 36 hours, wash it with deionized water for 5 to 7 times after soaking, put it into an oven for drying, and then grind and sieve it to obtain the preliminary treated resin.
[0022] The preliminary treated silica in step S1 is prepared by the following method: weigh silica raw materials as needed, crush, grind and sieve the silica raw materials to obtain silicon powder, send the silicon powder into a ball mill for ball milling, add a blending material during the ball milling process, and the mass of the blending material is 55-65% of the mass of the silicon powder. After the ball milling treatment is completed, the silicon powder is placed in an ultrasonic disperser for treatment, and the ultrasonic frequency is set to 60-100kHz and the time is 8-10min. After the ultrasonic treatment is completed, the preliminary treated silica is obtained.
[0023] The first mixed material in step S2 is prepared by the following method: corn starch is selected as a raw material, the corn starch is mixed with a copper sulfate solution, the concentration of the copper sulfate solution is 2-4%, the mass ratio of corn starch to copper sulfate solution is 1: (2-4), after the mixing reaction for 10-20 minutes, the first mixed material is obtained after filtering and drying.
[0024] The second mixed material in step S4 is prepared by the following method: glycerol and anhydrous ethanol are mixed, the concentration of glycerol is 5-7%, and the mass ratio of glycerol to anhydrous ethanol is 1: (4-6). After the mixing is completed, it is heated in a water bath to 65-75%, and kept warm for 15-25 minutes. Then corn starch is added, and the mass of corn starch is 60-70% of the glycerol. After adding, the temperature is raised to 85-95°C, and stirring is continued. After keeping warm and stirring for 8-12 minutes, it is waited to cool to room temperature to obtain the second mixed material.
[0025] In step S1, the preheating temperature of the oven is set to 55-65°C, and the temperature is raised to 90-100°C and then kept warm for 6-8 hours.
[0026] The formulation is prepared by the following method: maleic anhydride is mixed with a xylene solution, the concentration of the xylene solution is 20-40%, the mass ratio of maleic anhydride to the xylene solution is 1:(4-6), the mixture is allowed to stand for reaction for 40-50 minutes, and the reaction product is filtered, washed and dried to obtain the formulation.
[0027] The particle size of the initially treated resin after screening is ≤100μm.
[0028] The particle size of silica after preliminary treatment and ball milling is ≤75μm.
[0029] The mixing treatment method in step S6 is: mixing the first prepared material with the second prepared material, the mass ratio of the first mixed material to the second mixed material is 1: (0.5-0.7), and after mixing, sending them into an ultrasonic disperser for treatment, setting the ultrasonic frequency to 80-120 kHz, and the time to 12-16 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
[0030] In this embodiment, the silica raw material and the mesoporous resin raw material are preliminarily treated. After being soaked in a chromic acid solution, the mesoporous resin can undergo an oxidation-reduction reaction with the surface of the mesoporous resin by utilizing the corrosiveness of the chromic acid solution, so that the mesoporous resin is corroded to form a rich pore structure. During the ball milling process, the silica raw material is modified by the addition of a blending material and the silicon powder is modified by maleic anhydride. The anhydride groups in the maleic anhydride react with the hydroxyl groups on the surface of the silicon powder to form an ester bond, which can enhance the compatibility of the silicon powder with the preliminarily treated resin, so that the prepared mesoporous resin-based silicon-carbon precursor has good specific surface area performance, thereby improving the performance of the precursor in the subsequent preparation process. By adding the first mixed material, the first mixed material is prepared by adding corn starch as a raw material. After being treated with a copper sulfate solution, the corn starch can be effectively wrapped on the surface of the raw material to form a conductive coating. In the subsequent heating treatment, the corn starch is heated and gelatinized. The gelatinized conductive coating can be firmly attached to the surface of the powder raw material of the precursor, and has good wrapping properties, thereby improving the thermal stability of the precursor.
[0031] Based on the above embodiments, the inventors also conducted the following experiments:
[0032] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.
[0033] Experiment 1:
[0034] S1: Weigh the mesoporous resin as needed, crush it, and process it into granular mesoporous resin, then soak the mesoporous resin in chromic acid solution for 24 hours, wash it with deionized water 5 times after soaking, and put it into an oven for drying. The preheating temperature of the oven is set to 55°C, and the temperature is increased to 90°C and then kept warm for 6 hours. Then, grind and sieve the preliminary treated resin, and the particle size after sieving is ≤100μm, that is, the preliminary treated resin is obtained. Weigh the silica raw material as needed, crush, grind and sieve the silica raw material, and the particle size after ball milling is ≤75μm, to obtain silica Powder, sending silicon powder into a ball mill for ball milling treatment, during the ball milling process, adding a blending material, mixing maleic anhydride with a xylene solution, the concentration of the xylene solution is 20%, the mass ratio of maleic anhydride to the xylene solution is 1:4, and after mixing, standing for reaction for 40 minutes, filtering, washing, and drying the reaction product to obtain a blending material, the mass of the blending material is 55% of the mass of the silicon powder, and after the ball milling treatment is completed, the silicon powder is placed in an ultrasonic disperser for treatment, the ultrasonic frequency is set to 60kHz, and the time is 8 minutes. After the ultrasonic treatment is completed, the preliminary treated silica is obtained; S2: corn starch is selected as a raw material, and the corn starch is mixed with a copper sulfate solution, wherein the concentration of the copper sulfate solution is 2%, and the mass ratio of corn starch to the copper sulfate solution is 1:2, and after the mixing reaction for 10 minutes, the mixture is filtered and dried to obtain a first mixed material; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: Glycerol and anhydrous ethanol are mixed, the concentration of glycerol is 5%, and the mass ratio of glycerol to anhydrous ethanol is 1:4. After the mixing is completed, the mixture is heated to 65% in a water bath and kept warm for 15 minutes. Then corn starch is added, and the mass of corn starch is 60% of the glycerol. After the addition, the temperature is raised to 85°C and stirring is continued. After stirring and keeping warm for 8 minutes, the mixture is cooled to room temperature to obtain a second mixture. S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mix the first reserve material with the second reserve material, the mass ratio of the first mixed material to the second mixed material is 1:0.5, and after mixing, send them into an ultrasonic disperser for treatment, set the ultrasonic frequency to 80 kHz, and the time to 12 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
[0035] Experiment 2:
[0036] S1: Weigh the mesoporous resin as needed, crush it, and process it into granular mesoporous resin, then soak the mesoporous resin in chromic acid solution for 30 hours, wash it with deionized water 6 times after soaking, and put it into an oven for drying. The preheating temperature of the oven is set to 60°C, and the temperature is increased to 95°C and then kept warm for 7 hours. Then grind and sieve the preliminary treated resin, and the particle size after sieving is ≤100μm, that is, the preliminary treated resin is obtained. Weigh the silica raw material as needed, crush, grind and sieve the silica raw material, and the particle size after ball milling is ≤75μm, to obtain silica Powder, sending silicon powder into a ball mill for ball milling treatment, during the ball milling process, adding a blending material, mixing maleic anhydride with a xylene solution, the concentration of the xylene solution is 30%, the mass ratio of maleic anhydride to the xylene solution is 1:5, and after mixing, standing for reaction for 45 minutes, filtering, washing, and drying the reaction product to obtain a blending material, the mass of the blending material is 60% of the mass of the silicon powder, after the ball milling treatment is completed, the silicon powder is placed in an ultrasonic disperser for treatment, the ultrasonic frequency is set to 80kHz, the time is 9 minutes, and after the ultrasonic treatment is completed, the preliminary treated silica is obtained; S2: corn starch is selected as a raw material, and the corn starch is mixed with a copper sulfate solution, wherein the concentration of the copper sulfate solution is 3%, and the mass ratio of corn starch to the copper sulfate solution is 1:3, and the mixture is mixed and reacted for 15 minutes, and then filtered and dried to obtain a first mixed material; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: Glycerol and anhydrous ethanol are mixed, the concentration of glycerol is 6%, and the mass ratio of glycerol to anhydrous ethanol is 1:5. After the mixing is completed, the mixture is heated to 70% in a water bath and kept warm for 20 minutes. Then corn starch is added, and the mass of corn starch is 65% of the glycerol. After the addition, the temperature is raised to 90°C and stirring is continued. After the stirring is kept warm for 10 minutes, the mixture is cooled to room temperature to obtain a second mixture. S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mix the first reserve material with the second reserve material, the mass ratio of the first mixed material to the second mixed material is 1:0.6, and after mixing, send them into an ultrasonic disperser for treatment, set the ultrasonic frequency to 100 kHz, and the time to 14 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
[0037] Experiment 3:
[0038] S1: Weigh the mesoporous resin as needed, crush it, and process it into granular mesoporous resin, then soak the mesoporous resin in chromic acid solution for 36 hours, wash it with deionized water 7 times after soaking, and put it into an oven for drying. The preheating temperature of the oven is set to 65°C, and the temperature is increased to 100°C and then kept warm for 8 hours. Then grind and sieve the preliminary treated resin to a particle size of ≤100μm after sieving, and obtain the preliminary treated resin. Weigh the silica raw material as needed, crush, grind and sieve the silica raw material, and the particle size of the preliminary treated silica after ball milling is ≤75μm, and obtain silica Powder, sending silicon powder into a ball mill for ball milling treatment, during the ball milling process, adding a blending material, mixing maleic anhydride with a xylene solution, the concentration of the xylene solution is 40%, the mass ratio of maleic anhydride to the xylene solution is 1:6, and after mixing, standing for reaction for 50 minutes, filtering, washing, and drying the reaction product to obtain a blending material, the mass of the blending material is 65% of the mass of the silicon powder, and after the ball milling treatment is completed, the silicon powder is placed in an ultrasonic disperser for treatment, the ultrasonic frequency is set to 100kHz, and the time is 10 minutes. After the ultrasonic treatment is completed, the preliminary treated silica is obtained; S2: corn starch is selected as a raw material, and the corn starch is mixed with a copper sulfate solution, wherein the concentration of the copper sulfate solution is 4%, and the mass ratio of corn starch to the copper sulfate solution is 1:4, and the mixture is mixed and reacted for 20 minutes, and then filtered and dried to obtain a first mixed material; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: Glycerol and anhydrous ethanol are mixed, the concentration of glycerol is 7%, and the mass ratio of glycerol to anhydrous ethanol is 1:6. After the mixing is completed, the mixture is heated to 75% in a water bath and kept warm for 25 minutes. Then corn starch is added, and the mass of corn starch is 70% of the glycerol. After the addition, the temperature is raised to 95°C and stirring is continued. After the stirring is kept warm for 12 minutes, the mixture is cooled to room temperature to obtain a second mixture. S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mix the first reserve material with the second reserve material, the mass ratio of the first mixed material to the second mixed material is 1:0.7, and after mixing, send them into an ultrasonic disperser for treatment, set the ultrasonic frequency to 120 kHz, and the time to 16 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
[0039] Comparative Example 1: The difference between this comparative example and Experiment 1 is that: This comparative example does not contain a treating agent.
[0040] Comparative Example 2: The difference between this comparative example and Experiment 1 is that: In this comparative example, no formulation liquid was added when preparing the treatment agent.
[0041] Comparative Example 3: The difference between this comparative example and Experiment 1 is that: In this comparative example, no lecithin was added when preparing the formulation.
[0042] Comparative Example 4: The difference between this comparative example and Experiment 1 is that: In this comparative example, no citric acid was added when preparing the treating agent.
[0043] Performance test: The performance test was carried out on the mesoporous resin-based silicon-carbon precursor samples after being treated in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and the obtained test data were recorded in the following table: In the specific surface area test: the sample is pretreated under vacuum conditions to remove impurities and moisture adsorbed on the sample surface, and then a nitrogen adsorption and desorption experiment is carried out at low temperature. The specific surface area parameters of the mesoporous resin-based silicon-carbon precursor are calculated through the adsorption isotherm.
[0044] In the thermal stability test: a thermogravimetric analyzer was used for the test. 10 mg of sample was placed in the sample crucible of the thermogravimetric analyzer. Under a nitrogen atmosphere, the temperature was raised from room temperature to 1000°C at a heating rate of 10°C / min. The mass change curve of the sample during the heating process was recorded, and the residual rate parameters of the sample were analyzed.
[0045]
[0046] By comparing and analyzing the relevant data in the table, it can be seen that the mesoporous resin-based silicon-carbon precursor prepared by the present invention not only has good specific surface area performance, but also has good thermal stability. This shows that the preparation method of the mesoporous resin-based silicon-carbon precursor provided by the present invention has a broader market prospect and is more suitable for promotion.
[0047] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0048] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a mesoporous resin-based silicon-carbon precursor, characterized in that: The following steps are involved: S1: selecting a mesoporous resin raw material, and obtaining a preliminarily treated resin after treatment, and selecting a silica raw material, and obtaining a preliminarily treated silica after treatment; S2: preparing a first mixed material for standby use, wherein the first mixed material is prepared by the following method: selecting corn starch as a raw material, mixing the corn starch with a copper sulfate solution, wherein the mass ratio of the corn starch to the copper sulfate solution is 1:(2-4), mixing and reacting for 10-20 minutes, filtering, and drying to obtain the first mixed material; S3: mixing the preliminarily treated resin obtained in step S1 with the first mixed material obtained in step S2 to obtain a first standby material; S4: preparing a second mixed material for standby use, wherein the second mixed material is prepared by the following method: mixing glycerol and anhydrous ethanol, wherein the mass ratio of glycerol to anhydrous ethanol is 1:(4-6), heating in a water bath to 65-75% after the mixing is completed, and keeping the temperature for 15-25 minutes, then adding corn starch, wherein the mass of the corn starch is 60-70% of the glycerol, heating to 85-95° C. after the addition, continuing to stir, keeping the temperature for 8-12 minutes, and waiting to cool to room temperature, thus obtaining the second mixed material; S5: mixing the preliminarily treated silica obtained in step S1 with the second mixed material obtained in step S4 to obtain a second standby material; S6: Mixing the first prepared material obtained in step S3 with the second prepared material obtained in step S5 to obtain a mesoporous resin-based silicon-carbon precursor.
2. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 1, characterized in that: The preliminary treated resin in step S1 is prepared by the following method: weighing mesoporous resin as needed, crushing it into granular mesoporous resin, then soaking the mesoporous resin in chromic acid solution for 24 to 36 hours, washing it with deionized water for 5 to 7 times after soaking, putting it into an oven for drying, and then grinding and sieving to obtain the preliminary treated resin.
3. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 1, characterized in that: The preliminary treated silica in step S1 is prepared by the following method: weigh silica raw materials as needed, crush, grind and sieve the silica raw materials to obtain silicon powder, send the silicon powder into a ball mill for ball milling, add a blending material during the ball milling process, the mass of the blending material is 55-65% of the mass of the silicon powder, and after the ball milling treatment is completed, place the silicon powder in an ultrasonic disperser for treatment, set the ultrasonic frequency to 60-100kHz, and the time to 8-10min. After the ultrasonic treatment is completed, the preliminary treated silica is obtained.
4. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 1, characterized in that: The concentration of the copper sulfate solution is 2-4%.
5. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 1, characterized in that: The concentration of the glycerol is 5-7%.
6. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 2, characterized in that: In step S1, the preheating temperature of the oven is set at 55-65° C., and the temperature is raised to 90-100° C. and then kept warm for 6-8 hours.
7. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 3, characterized in that: The formulation is prepared by the following method: maleic anhydride is mixed with a xylene solution, the concentration of the xylene solution is 20-40%, the mass ratio of the maleic anhydride to the xylene solution is 1:(4-6), the mixture is allowed to stand for reaction for 40-50 minutes, and the reaction product is filtered, washed and dried to obtain the formulation.
8. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 2, characterized in that: The particle size of the preliminarily treated resin after screening is ≤100 μm.
9. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 3, characterized in that: The particle size of the preliminarily treated silica after ball milling is ≤75 μm.
10. The method for preparing a mesoporous resin-based silicon-carbon precursor according to claim 1, characterized in that: The mixing treatment method in step S6 is: mixing the first prepared material with the second prepared material, wherein the mass ratio of the first mixed material to the second mixed material is 1:(0.5-0.7), and after mixing, the mixed materials are sent into an ultrasonic disperser for treatment, and the ultrasonic frequency is set to 80-120 kHz and the time is 12-16 minutes. After completing the ultrasonic treatment, a mesoporous resin-based silicon-carbon precursor is obtained.
Citation Information
Cited By
Biomass composite precursor, hard carbon negative electrode material and preparation methods of biomass composite precursor and hard carbon negative electrode material
CN121800173A